2010
DOI: 10.7326/0003-4819-152-12-201006150-00003
|View full text |Cite
|
Sign up to set email alerts
|

Extended Valganciclovir Prophylaxis to Prevent Cytomegalovirus After Lung Transplantation

Abstract: In adult lung transplant recipients who have received 3 months of valganciclovir, extending prophylaxis by an additional 9 months significantly reduces CMV infection, disease, and disease severity without increased ganciclovir resistance or toxicity. A beneficial effect with regard to prevention of CMV disease seems to extend at least through 18 months after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
188
6
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(209 citation statements)
references
References 28 publications
13
188
6
2
Order By: Relevance
“…CMV disease incidence was 16.9% in high-risk patients (CMV Dþ/RÀ) and 4.4% in the intermediate-risk patients (CMV Rþ). These numbers are similar to or lower than those observed in the most recent published prospective cohort studies (9,26) or randomized controlled trials (15,16,27), reflecting the improved management on the prevention of CMV disease over the last years. Some patients took sequentially more than one drug, so the addition of numbers may result in >100%.…”
Section: Discussionmentioning
confidence: 45%
“…CMV disease incidence was 16.9% in high-risk patients (CMV Dþ/RÀ) and 4.4% in the intermediate-risk patients (CMV Rþ). These numbers are similar to or lower than those observed in the most recent published prospective cohort studies (9,26) or randomized controlled trials (15,16,27), reflecting the improved management on the prevention of CMV disease over the last years. Some patients took sequentially more than one drug, so the addition of numbers may result in >100%.…”
Section: Discussionmentioning
confidence: 45%
“…23 We hypothesized that transplant confers 1-year physical and mental health QOL benefi ts and sought to determine whether these benefi ts vary by sex, native disease, age, or type of transplant operation.…”
Section: Discussionmentioning
confidence: 99%
“…Trial design and enrollment criteria have been published elsewhere. 23 Inclusion in the QOL analysis required patients to have completed one or more QOL measures post lung transplant. Five randomized patients did not complete any QOL measures after lung transplantation and, therefore, were excluded ( Fig 1 depicts the study cohort).…”
Section: Qol Study Cohortmentioning
confidence: 99%
“…A metaanalysis of 11 randomized trials (698 patients; median follow-up: 12 months, range: 3-22 months), with six randomized trials (302 patients) after kidney transplantation, demonstrated a beneficial effect of the prophylactic use of CMV immunoglobulin on total survival and prevention of Should not be used 1500 mg once a day, or 500 mg three times a day Should not be used 1000 mg once a day, or 500 mg twice a day [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Should not be used 500 mg once a day <10…”
Section: Antiviral Medications For Universal Prophylaxis and Preemptimentioning
confidence: 99%